Oral Candida Albicans Colonization In Denture Wearer: A Literature Review - Febriane Balafif, Felisha; Rafisa, Anggun; Kuswandani, Faisal; Najmi, Nuroh (Sean Institute, 2024)
Denture stomatitis is the most prevalent multifactorial, chronic inflammatory oral condition amongs denture wearers. One of the primary roles of dentures in denture stomatitis is their potential to cause irritation and inflammation of the oral tissues. This continuous irritation creates an environment where fungal infections, notably C. albicans. The traumatic factors such as mechanical trauma caused by loose prosthesis can increase the risk of tissue penetration and colonization of Candida species. This literature review aimed to explore the colonization of C. albicans in the denture wearer. The article was conducted of two databases and were limited to the period from 2019 to 2024 with a combination of the following keywords: “oral Candida albicans”